Environmental burdens of the comprehensive utilization of straw: Wheat straw utilization from a life-cycle perspective. (20th June 2020) - Sun, Mingxing; Xu, Xiangbo; Wang, Chengdong; Bai, Yunli; Fu, Chao; Zhang, Linxiu; Fu, Rao; Wang, Yutao
Abstract: Agricultural straw utilization has become a big concern in many countries with abundance of the production. While different comprehensive utilization methods have been proposed, the environmental aspects of these methods need to be examined to reduce the environmental burdens of agricultural straw disposal. By deploying life cycle assessment, this article evaluates the environmental impact of different wheat straw utilization methods, including soil incorporation, open burning, indoor incineration with energy recovery, combined electricity and energy recovery, conventional straw pulping, and a new type of straw pulping. The results show that the new type of straw pulping has the best environmental performance, while open burning has the worst. The performance of the new type of straw pulping is mainly attributed to its substitution for sulphate pulp and chemical fertilizers. New type of straw pulping has the best environmental performance for human health, ecosystem quality and resource impact categories, with corresponding −2.08E-03 DALY (Disability-Adjusted Life Years),  −1.50E+03 PDF·m 2 ·y (Potentially Disappeared Fraction of species over a certain amount of m 2 during a certain amount of years) and −7.75E+03 MJ (Mega Joules) for these three impact categories. While soil incorporation has the smallest environmental impact in global warming impact category, with 2.33E+02 kg CO2 -eq. Sound management of agricultural straw should combine different utilization methods. Policy interventions, such as high-quality straw leaving the field, are needed to deal with the substantial generation of agricultural straw. Graphical abstract: Image 1 Highlights: Six wheat straw utilization methods are evaluated. Life cycle assessment are deployed for the evaluation. A new type of straw pulping has the best environmental performance. Policy interventions are needed to foster sound utilization of straw.